2010
DOI: 10.1007/s11605-009-1009-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Percutaneous Preoperative Biliary Drainage in Patients with Suspected Hilar Cholangiocarcinoma

Abstract: Introduction Controversy exists over the preferred technique of preoperative biliary drainage (PBD) in patients with hilar cholangiocarcinoma (HCCA) requiring major liver resection. The current study compared outcomes of endoscopic biliary drainage (EBD) and percutaneous transhepatic biliary drainage (PTBD) in patients with resectable HCCA. Methods One hundred fifteen consecutive patients were explored for HCCA between 2001 and July 2008 and assigned by initial PBD procedure to either EBD or PTBD. Results Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
150
2
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 38 publications
3
150
2
7
Order By: Relevance
“…Cholecystitis due to the obstruction of cystic duct or pancreatitis due to the obstruction of main pancreatic duct are also potential causes of fever. In such cases, CT examination is useful for the diagnosis [76,78,82,83].…”
Section: Cq11: What Is the Best Treatment For Fever In Patients Who Hmentioning
confidence: 99%
“…Cholecystitis due to the obstruction of cystic duct or pancreatitis due to the obstruction of main pancreatic duct are also potential causes of fever. In such cases, CT examination is useful for the diagnosis [76,78,82,83].…”
Section: Cq11: What Is the Best Treatment For Fever In Patients Who Hmentioning
confidence: 99%
“…EBD in patients affected by tumors of proximal bile duct is often a difficult maneuver, affected by a high failure rate, which may require the association of more than one drainage techniques (usually PTBD). Moreover, after the procedure, evaluation of tumor length and extension may be less accurate in the presence of one or more stents and for local inflammation and fibrosis [8,9]. EBD is affected by an higher rate of postprocedural complications compared to other techniques, with an overall 25-50% morbidity and 3-5% mortality rate [9,10].…”
Section: Drainage Techniquesmentioning
confidence: 99%
“…This technique consists of selectively cannulating the bile duct by a percutaneous approach, usually under ultrasound guide, and placement of one or more biliary stents in the biliary system. It has been reported that the post-procedural morbidity rate of percutaneous techniques is lower compared to the endoscopic technique [9]. PTBD is a direct approach for bile duct decompression in patient with HC and it is usually the procedure of choice in most groups due to effectiveness in decreasing serum bilirubin with low rates of cholangitis [9,10].…”
Section: Drainage Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…В отечественной литературе имеется небольшое количест-во публикаций, посвященных проблеме эндоскопического стентирования, что, ве-роятно, связано с ещѐ недостаточно ши-роким применением данного способа де-компрессии в отечественных хирургиче-ских клиниках. Зарубежные авторы, в свою очередь, отмечают высокую эффек-тивность данного способа декомпрессии, а также малое количество послеопераци-онных осложнений [10].…”
unclassified